Differences in the rotation angles of the upper, middle, and lower thoracic spine, lumbar spine, and pelvis during front crawl swimming - Ogata, T.; Takabayashi, T.; Toma, H.; Kikumoto, T.; Kubo, M. (Sports Biomechanics, 2025)
Body roll during front crawl swimming refers to spinal rotation along the longitudinal axis. It is typically evaluated at the shoulders and pelvis; however, the middle and lower thoracic and lumbar spine are overlooked. Therefore, we aimed to investigate the differences in rotation angles and peak timing across the upper (shoulder roll), middle and lower thoracic spine, lumbar spine, and pelvis (hip roll) during front crawl swimming. This study included 16 healthy swimmers. Participant had five inertial measurement units attached to the spinous processes and performed a 50 m front crawl swim. We measured and compared peak rotation angle and timing on the breathing side across the spinal segments. The upper thoracic spine (67.5 ± 13.6°) exhibited the greatest rotation, followed by the middle thoracic (55.2 ± 13.6°), which exceeded the lower thoracic (46.1 ± 12.2°), lumbar spine (46.3 ± 11.7°), and pelvis (46.5 ± 9.0°). No significant differences were found among angles of lower thoracic spine, lumbar spine, and pelvis, nor in peak timing across all segments. A significant positive correlation was observed between thoracic torsion and upper thoracic rotation angles. Study findings highlighted the importance of evaluating the middle thoracic spine along with shoulder and hip roll.